1974
DOI: 10.1021/jo00918a026
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of bond lengths and angles of hydrocarbons by the iterative MOA [maximum overlap approximation] method

Abstract: The bond lengths and angles of some characteristic strained cyclic and polycyclic alkanes and alkenes were calculated by the iterative maximum overlap approximation (IMOA) procedure. The agreement with experimental bond lengths and angles is satisfactory indicating that IMOA method might be useful for a semiquantitative prediction of the geometry of hydrocarbons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
19
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(23 citation statements)
references
References 1 publication
4
19
0
Order By: Relevance
“…§ Calculated using %s =0.20 ~JcH (Muller & Pritchard, 1959). ¶ lterative molecular-orbital overlap (IMOA) method: Kovacevic & Maksic (1974);Eckert-Maksic & Maksic (1982).…”
Section: Exocyclic Bondingmentioning
confidence: 99%
See 1 more Smart Citation
“…§ Calculated using %s =0.20 ~JcH (Muller & Pritchard, 1959). ¶ lterative molecular-orbital overlap (IMOA) method: Kovacevic & Maksic (1974);Eckert-Maksic & Maksic (1982).…”
Section: Exocyclic Bondingmentioning
confidence: 99%
“…§ Taken from Breitmaier & Voelter (1978). ¶ See footnote § of Table 8. II Kovacevic & Maksic (1974). Eckert-Maksic & Maksic (1982).…”
Section: Ring Geometrymentioning
confidence: 99%
“…The deviation angles in C,, and C,, clusters are the largest in value, but these angles are still smaller than that of 26.8" in cyclopropene [8]. The average deviation angles in C, and C,,, are smaller and equal, respectively, to the deviation angle of the double bond in cyclobutene (13.3') [4].…”
mentioning
confidence: 84%
“…The clusters studied are CZ4, C,,, C, , and Ciz0, which have the shape of the truncated octahedron, truncated cuboctahedron, truncated icosahedron, and truncated icosidodecahedron, respectively. The shapes of these clusters together with the enumeration of their atoms are depicted in Figure 1.The method used is the iterative maximum overlap approximation (IMOA) [4]. It considers the orthogonal local hybrid orbitals…”
mentioning
confidence: 99%
“…Distortions from cubic symmetry are of interest. Although various theoretical studies of the cubane geometry have been reported (1)(2)(3)(4), no structure determinations of cubane derivatives other than that of cubane itself ( 5 ) are available.…”
Section: Introductionmentioning
confidence: 99%